BARRIERS TO SUSTAINABLE GREEN BUILDING PRACTICE IN NIGERIA (FUDMA JOURNAL OF SCIENCES, 2024)
Green building approaches are becoming increasingly essential in the construction business. Green building entails designing buildings and employing methods that are ecologically responsible and efficient with resources throughout the life cycle of the building. It is viewed as a substitute to reducing or eliminating the negative environmental and climate change impacts of construction activities. Despite its benefits, green building uptake is hampered by a number of impediments. The study was conducted in the states of Abuja and Lagos, focusing on professionals, freelancers, and clients. The collected data was analyzed using SPSS 25.0, and the study's findings revealed that lack of understanding of Green Building Technologies was ranked first among the obstacles to green building acceptance with a RII of 0.79, followed by a lack of institutions to develop policies and set guidelines with a RII of 0.77, ambiguity with green equipment and materials with a RII of 0.76, lack of interest and interaction among project team members with 0.76, and lack of interest as well as communication among project team members with RII of 0.76.However, there are various hurdles to the implementation of ecologically conscious building in Nigeria. Long design and approval procedures for new technologies, a shortage of sustainable materials and goods, a proclivity to stick with present practices, a lack of building norms and regulations, and a lack of awareness about green products and powerful building systems are all examples. To guarantee a smooth transition to green building, industry players should investigate and apply sustainable solutions, particularly throughout...
Keywords: Climate Change; Environment; Green Building Practice; Integrated Innovation Design; Sustainable Design